Hydroxychloroquine Induced Retinopathy: A Case Series - Maryam Mobini; Ahmad Ahmadzadeh-Amiri; Soghra Khani (علوم بهداشتی ایران)
Background and Purpose: Occular toxicity is one of the most important complications of Hydroxychloroquine. Not any type of treatment has so far been found and recommended for this disorder. The purpose of this study was to report some characteristics of patients with Hydroxychloroquine Induced Retinopathy.